Long-Term Course of Humoral and Cellular Immune Responses in Outpatients After SARS-CoV-2 Infection - Schiffner, Julia; Backhaus, Insa; Rimmele, Jens; Schulz, Sören; Möhlenkamp, Till; Klemens, Julia Maria; Zapf, Dorinja; Solbach, Werner; Mischnik, Alexander (Frontiers in Public Health, 2021)
Characterisation of the naturally acquired B and T cell immune responses to SARS-CoV-2 is important for the development of public health and vaccination strategies to manage the burden of COVID-19 disease. We conducted a prospective, cross-sectional analysis in COVID-19 recovered patients at various time points over a 10-month period in order to investigatedetermine how circulating antibody levels and interferon-gamma (IFN-γ) release by peripheral blood cells change over time following natural infection. From March 2020 till January 2021, we enrolled 412 adults mostly with mild or moderate disease course. At each study visit, subjects donated peripheral blood for testing of anti-SARS-CoV-2 IgG antibodies and IFN-γ release after SARS-CoV-2 S-protein stimulation. Anti-SARS-CoV-2 IgG antibodies were positive identified in 316/412 (76.7 %) and borderline in 31/412 (7.5 %) of the patients. Our confirmation assay for the presence of neutralizing antibodies was positive in 215/412 (52.2 %) and borderline in 88/412 (21.4 %) of all patients. and 215/412 (52.2%) had positive neutralizing antibody levels. Likewise, in 274/412 (66.5 %) positive IFN-γ release and IgG antibodies were detected. With respect to time after infection, both IgG antibody levels and IFN-γ concentrations decreased by about half within three hundred days. Statistically, IgG and IFN-γ production were closely associated, but on an individual basis we observed patients with high antibody titres but low IFN-γ levels and vice versa. Our data suggest that immunological reaction is acquired in most individuals after natural infection with SARS-CoV-2 and is sustained in the majority of patients for at least ten10 months after infection after mild or moderate disease course. Since no robust marker for protection against COVID-19 exists so far, we recommend utilizing both, IgG and IFN-γ release for an individual assessment of the immunity status.